Experience of Breastfeeding Mothers in Providing Exclusive Breastfeeding in Lambangsari Village, Bojonegara District - Silvia; Nofa Anggraini (Global Writing Academica Researching and Publishing, 2023)
Breast milk can provide a better life for babies, breast milk will protect babies from various types of diseases or viruses. Information on the coverage of infants aged less than 6 months who receive exclusive breastfeeding in Banten Province in 2020 is 68.84%. However, this data has not been able to reach the government program target of 80%. The purpose of this study was to find out the experiences of breastfeeding mothers in providing exclusive breastfeeding in Lambangsari Village, Kec. Bojonegara. The design of this research is analytic observational research. Researchers observed and looked for the relationship between the variables of husband's support, support from health workers and knowledge, to exclusive breastfeeding. The research approach used in this study is cross-sectional. The population in this study were breastfeeding mothers who had babies aged 6-12 months in Lambangsari Village, Bojonegara District, totaling 424 people. The required sample is 81 respondents. The sampling technique for respondents used a simple random sampling technique. The instrument in this study was to use a questionnaire. Researchers used the Chi Square test with a confidence level of 95% or a significance level of 5%. The research results show that the P value of husband's support = 0.021; P value Support of health workers = 0.000; and P value of knowledge = 0.000, the conclusion is that p value < (0.05) so there is a relationship between husband support, health workers and knowledge of exclusive breastfeeding in Lambangsari Village, Bojonegara District.